2012
DOI: 10.3846/mla.2011.05
|View full text |Cite
|
Sign up to set email alerts
|

Composite Dos Attack Model

Abstract: Preparation for potential threats is one of the most important phases ensuring system security. It allows evaluating possible losses, changes in the attack process, the effectiveness of used countermeasures, optimal system settings, etc. In cyberattack cases, executing real experiments can be difficult for many reasons. However, mathematical or programming models can be used instead of conducting experiments in a real environment. This work proposes a composite denial of service attack model that combines band… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…In this case, the remaining part of traffic could be blocked by its filtering system. Other works on threats and attacks with emphasis on evaluation analysis of DoS traffic have been studied in [22], [23]. This paper observed that existing works in literature regarding cyber security vis-à-vis DoS and other schemes have not explored embedded Stateful Packet Inspection (SPI) based on OpenFlow Application Centric Infrastructure (OACI) for securing enterprise systems and their networks such as SGEMS architecture.…”
Section: Related Research Effortsmentioning
confidence: 96%
See 2 more Smart Citations
“…In this case, the remaining part of traffic could be blocked by its filtering system. Other works on threats and attacks with emphasis on evaluation analysis of DoS traffic have been studied in [22], [23]. This paper observed that existing works in literature regarding cyber security vis-à-vis DoS and other schemes have not explored embedded Stateful Packet Inspection (SPI) based on OpenFlow Application Centric Infrastructure (OACI) for securing enterprise systems and their networks such as SGEMS architecture.…”
Section: Related Research Effortsmentioning
confidence: 96%
“…The properties of an attack as explained previously could be used to ascertain its effect on QoS. In [22], a good mathematical expression for calculating the success of DoS attack using the known data on the attacks, normal flow and other properties of the victim is described but this paper models the security QoS metrics for VBDDA using the SPI-OACI approach. In this case, when a DDoS/ DRDoS resource depletion attacks occurs, this will facilitate an attacker sending packets that misuse network protocol communications or sending malformed packets that tie up network resources so that none are left for legitimate users or the server backend at large.…”
Section: Vulnerability Bandwidth Depletion Ddos Attack (Vbdda)mentioning
confidence: 99%
See 1 more Smart Citation
“…; • network and application level simulators -they are designed to simulate sensor network and mainly to test routing algorithms; • cross level simulators -this category represents tools able to simulate devices and network at various levels of abstraction: routing algorithms, energy and resource consumption and simple applications. The last group contains the most all-purpose toolssome representative are as follows: COOJA [13], J-Sim and Sensor Network Package [14], CupCarbon [15]. The other group is made up of simulators which base upon COTS software (Commercial Off-The-Shelf Software), like NS2 or OMNET++.…”
Section: Software Tool For Modelling and Simulation Dos Threatsmentioning
confidence: 99%
“…To present "in action" the developed simulation software, an experiment regarding DoS attack was carried out. Similarly to [15] we considered a "denial of service" attack case in order to simultaneously simulate hybrid model composed of bandwidth exhaustion, filtering and memory depletion sub-models. The main target of the "denial of service" attack is RFID office system is order to ultimately reduce or finally block legitimate RFID devices (RFIDDevs) from accessing services of RFID tagged document flow management system (RFIDSys).…”
Section: Example Of Dos Attack Experimentsmentioning
confidence: 99%